Effects of added exogenous hormones on lactation-related physiological functions of equine mammary epithelial cells - Li, Chao; Zheng, Shengchen; Lin, Jianwei; Li, Qian; Yang, Kailun; Li, Xiaobin (Frontiers in Veterinary Science, 2025)
This study aimed to optimize the culture conditions for equine mammary epithelial cells (EMECs) by investigating the effects of fetal bovine serum (FBS), hydrocortisone (HYD), insulin (INS), and epidermal growth factor (EGF) on cell growth and function. The primary objectives were to identify the optimal culture conditions for EMECs, evaluate the impact of FBS, HYD, INS, and EGF on cell viability and milk component synthesis, and uncover genes involved in mare lactation and milk production. The optimal FBS concentration for cell survival was determined to be 15%, with further improvements achieved through the individual addition of 1 μg/mL HYD, 5 μg/mL INS, and 5 ng/mL EGF. Orthogonal analysis revealed that the combination of 1 μg/mL HYD and 5 ng/mL EGF resulted in the highest survival rates. This combination significantly increased triglyceride and lactose production by 86.36% and 33.33%, respectively (P < 0.01), and β-casein levels by 30.10% (P < 0.05), compared to the control. Transcriptome sequencing identified 596 upregulated and 432 downregulated genes, including laminin subunits (LAMA2, LAMA3, LAMA4, LAMA5), laminin gamma-1 (LAMC1), collagen type IV α1 chain (COL4A1), fatty acid synthase (FASN), and forkhead box protein O1 (FOXO1). Functional enrichment analysis highlighted key pathways related to cell adhesion, bioadhesion, cell-cell signaling, ECM-receptor interactions, and the PI3K-Akt signaling pathway. These findings demonstrate that the addition of HYD, INS, and EGF, both individually and in combination, enhances EMEC viability and milk component synthesis, offering new insights into the molecular mechanisms of mare lactation and milk production.